PENGARUH PROFITABILITAS, RISIKO KEUANGAN DAN PRICE EARNING RATIO (PER) TERHADAP PERATAAN LABA (INCOME SMOOTHING) PADA INDUSTRI PERKEBUNAN YANG LISTING DI BURSA EFEK INDONESIA - Dhistianti Mei Rahmawan Tari (Jurnal Manajemen Bisnis Krisnadwipayana, 2016)
This study aimed to investigate the effect of profitability, financial risk and PER on smoothing earnings (Income Smoothing) on Plantation Industries. The data used is secondary data. The number of companies in this study were four plantation company, PT Astra Agro Lestari Tbk (AALI), Gozco Plantations Tbk (GZCO), PT London Sumatra Indonesia Tbk (LSIP), PT Sinar Mas Agro Resources and Techlology, Tbk (SMAR) , with the observation period during the years 2008 to 2014. Methods of data analysis using multiple regression analysis. The findings in this study indicate that profitability, financial risk, and PER simultaneously have a positive and significant impact on the practice of income smoothing (income smoothing). Profitability is partially has a positive and significant impact on the practice of income smoothing (income smoothing). Financial risk partially has a positive and significant impact on the practice of income smoothing (income smoothing). PER partially have a positive influence and significance of the practice of income smoothing (income smoothing).